Meaning of parenting as a teenager - Carolina Antolinez Figueroa (Universidad de Antioquia, 2017)
Objective. Describe the meaning of parenting as a teenager. Methods. Study of the qualitative approach with phenomenological approach in the fourth village of San Cristobal (Bogotá, Colombia). The information was obtained by means of semi-structed interviews, participant observation, photos, daily and focal groups field. The information analysis was performed using the phenomenological method of Amadeo Giorgi. Results. The meaning of  their parenthood in the adolescentsrevealed five units of sense: emotional ambivalence, paternity as a process of learning, changes in lifestyle, making a life project and support networks. Conclusion. Teenage fatherhood was interpreted by the participants as a positive change and assumed a patriarchal perspective.